Costs, length of stay, and mortality of super‐refractory status epilepticus: A population‐based study from Germany. (6th July 2017) - Strzelczyk, Adam; Ansorge, Sonja; Hapfelmeier, Jana; Bonthapally, Vijayveer; Erder, M. Haim; Rosenow, Felix
Summary: Objective: Super‐refractory status epilepticus (SRSE) is a severe condition in which a patient in status epilepticus (SE) for ≥24 h does not respond to first‐, second‐, or third‐line therapy. The economic impact of SRSE treatment remains unclear. A health insurance research database was used for a population‐based estimation of SRSE‐associated inpatient costs, length of stay, and mortality in Germany. Methods: An algorithm using International Classification of Diseases, 10th Edition coding and treatment parameters identified and classified patients in a German statutory health insurance database covering admissions from 2008 to 2013 as having refractory SE (RSE) or SRSE. Admissions data in our study refer to these classifications. Associated patient data included costs, procedures, and demographics. Results: The algorithm identified 2, 585 (all type) SE admissions, classified as 1, 655 nonrefractory SE (64%), 592 (22.9%) RSE, and 338 (13.1%) SRSE, producing database incidence rates of 15.0 in 100, 000, 5.2 in 100, 000, and 3.0 in 100, 000 per year, respectively. Median cost per admission was €4, 063 for nonrefractory SE, €4, 581 (p < 0.001) for RSE, and €32, 706 (p < 0.001) for SRSE. Median length of stay varied significantly between 8 days (mean = 13.6) in nonrefractory SE, 14 days in RSE, and up to 37 days in SRSE. Discharge mortality increased from 9.6% in nonrefractory SE to 15.0% (p < 0.001) in RSE and 39.9% (p < 0.001) in SRSE. Significance: This study evaluated the hospital treatment costs associated with admissions classified by the algorithm as SRSE in Germany. SRSE represented 13% of all SE admissions, but resulted in 56% of all SE‐related costs. The lack of approved treatments and limited number of evidence‐based treatment guidelines highlight the need for further evaluations of the SRSE burden of illness and the potential for further optimization of treatments for SRSE.